Achieving prominent strengthening efficiency of graphene nanosheets in Al matrix composites by hybrid deformation. (15th October 2021) - Pu, Bowen; Zhang, Xiang; Zhao, Dongdong; He, Chunnian; Shi, Chunsheng; Liu, Enzuo; Sha, Junwei; Zhao, Naiqin
Abstract: Achieving uniform reinforcement dispersion and strong interfacial bonding remains challenging to increase the strengthening efficiency in advanced metal matrix composites (MMCs). In this work, we report the prominent strengthening efficiency in graphene nanosheet reinforced Al matrix (GNS/Al) composites fabricated via hybrid deformation combining hot extrusion and multi-pass hot rolling (MPHR). Results show that most GNS-rich zones in extruded GNS/Al composites were eliminated by MPHR, leading to an even layer-distribution of GNSs aligning along the Al grains, which initiates grain recrystallization and promotes dislocation accumulation for a high strain hardening of the composites. Moreover, the shear stress induced by MPHR was revealed to exfoliate overlapped GNSs to attach with Al and enhance the formation of boundary-like defects/disorders at the edge of GNSs, which promotes Al–C interdiffusion and generates the typically infiltrated Al-GNS interfaces featured by transition zones. Such unique interface structure exhibits a high interfacial shear strength, enabling the effective load transfer between GNSs and Al. It is confirmed that the fine distribution of GNS and robust Al-GNS interfacial cohesion contribute to the remarkable strengthening efficiency of GNSs. The present work paves a new way to disperse GNSs and tune interface structures for enhancing mechanical performance of Al matrix composites. Graphical abstract: Image 1